OCCURRENCE OF MACROALGAE FROM THE ULVA GENERA (ULVACEAE; CHLOROPHYTA) IN THE WIELKOPOLSKA REGION - Rybak, Andrzej; Messyasz, Beata (Poznańskie Towarzystwo Przyjaciół Nauk, 2009)
The work presents the specification of the reports from the appearance of species from Ulva genera (Ulvaceae, Chlorophyta) in the Wielkopolska region. The stands of the three species (Ulva compressa, U. intestinalis and U. prolifera) were marked on the map of the region in the ATPOL squares sequence. Since seventies till 2008 thalluses of the Ulva genera have been noticed in the 10 stands. Ulva species occurred in the lakes, ponds and rivers localized in the central part of the Wielkopolska region, often in the vicinity of the urbanized area.
Keywords: Ulva; Chlorophyta; Macroalgae mats; Distribution; Wielkopolska; Freshwater ecosystems; Freshwater Ulva; Freshwater Enteromorpha; Enteromorpha; Ulvaceae; Ulvophyceae; Greea algae; Macroalgae; Green tides